2021
DOI: 10.1021/acs.cgd.0c01403
|View full text |Cite
|
Sign up to set email alerts
|

Controlling CaCO3Particle Size with {Ca2+}:{CO32–} Ratios in Aqueous Environments

Abstract: The effect of stoichiometry on the new formation and subsequent growth of CaCO 3 was investigated over a large range of solution stoichiometries (10 –4 < r aq < 10 4 , where r aq = {Ca 2+ }:{CO 3 2– }) at various, initially constant degrees of supersaturation (30 < Ω cal < 200, where Ω … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 117 publications
(214 reference statements)
3
12
0
Order By: Relevance
“…Barite new formation was observed here to be faster, resulting in larger (prenucleation) clusters being observed earlier at ideal and barium-limited conditions (Figures and ). A similar nonsymmetrical dependence of crystal new formation on solution stoichiometry was previously reported by Seepma et al for CaCO 3 . For both BaSO 4 and CaCO 3 , the combined process of nucleation and growth is greatly hindered at nonstoichiometric conditions compared to pure crystal growth of these minerals under ideal 1:1 conditions, ,,, but in our case more by the lack of anions than cations.…”
Section: Resultssupporting
confidence: 87%
See 2 more Smart Citations
“…Barite new formation was observed here to be faster, resulting in larger (prenucleation) clusters being observed earlier at ideal and barium-limited conditions (Figures and ). A similar nonsymmetrical dependence of crystal new formation on solution stoichiometry was previously reported by Seepma et al for CaCO 3 . For both BaSO 4 and CaCO 3 , the combined process of nucleation and growth is greatly hindered at nonstoichiometric conditions compared to pure crystal growth of these minerals under ideal 1:1 conditions, ,,, but in our case more by the lack of anions than cations.…”
Section: Resultssupporting
confidence: 87%
“…On top of that, crystals nucleated and grew under constantly changing conditions within one experiment because Ω barite dropped, to a lesser extent I dropped and, at extreme r aq , r aq shifted toward more extreme values by several magnitudes as well. This was previously discussed for similar experiments with CaCO 3 by Seepma et al These changing conditions likely have caused more heterogeneity with regard to crystal formation rates and morphology over time during batch DLS experiments and were also not accounted for.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…In particular, the different concentrations employed in other publications lead to a different Ca 2+ /CO 3 2− activity ratio at the nucleation stage. This effect has been pointed out as a crucial variable during calcite formation [27][28][29]. The values calculated from these different experiments show remarkable consistency, assuming an experimental error of about 0.1 units that derive from the intrinsic criticisms presented in the Results.…”
Section: The Effect Of Ph and Ionic Strength On The Saturation State Of Calcitementioning
confidence: 53%
“…The presence of different precursors means that the system is taking a different pathway when precipitating the final solid phase; the various experimental conditions lead to unique nucleation pathways. For both the calcium phosphates and carbonates, it has been shown that the initial solution stoichiometry is critical in determining the nucleation and growth processes, even when controlling other parameters. , The ratio of precursor ions in solution, at least in part, controls which nucleation mechanism is available. Such a result further underlines the complex nature of nucleation.…”
mentioning
confidence: 99%